Mamlakat INNOVATIVE APPROACH OF TEACHING ENGLISH LANGUAGE: INNOVATIVE APPROACH OF TEACHING ENGLISH LANGUAGE - Ismoilova, Mamlakat (Журнал иностранных языков и лингвистики, 2022)
This article analyses the innovative and quite interesting methods we have in teaching English language. We may have a number of teaching methods in between traditional and modern. Everybody has their own understanding and conclusions on teaching English language. But this paper portrays combining this two types how we can make our teaching very effective. We have been completely bounded with traditional methods of teaching and understanding where the present day learners felt uncomfortable a bit. Learner’s mind will never be static it is ever growing and ever changing.